Perceived Costs versus Actual Benefits of Demographic Self‐Disclosure in Online Support Groups - Pechmann, Cornelia (Connie); Yoon, Kelly Eunjung; Trapido, Denis; Prochaska, Judith J. (Journal of Consumer Psychology, 2021)
Millions of U.S. adults join online support groups to attain health goals, but the social ties they form are often too weak to provide the support they need. What impedes the strengthening of ties in such groups? We explore the role of demographic differences in causing the impediment and demographic self‐disclosure in removing it. Using a field study of online quit‐smoking groups complemented by three laboratory experiments, we find that members tend to hide demographic differences, concerned about poor social integration that will weaken their ties. However, the self‐disclosures of demographic differences that naturally occur during group member discussions actually strengthen their ties, which in turn facilitates attainment of members’ health goals. In other words, social ties in online groups are weak not because members are demographically different, but because they are reluctant to self‐disclose their differences. If they do self‐disclose, this breeds interpersonal connection, trumping any demographic differences among them. Data from both laboratory and field about two types of demographic difference—dyad‐level dissimilarity and group‐level minority status—provide convergent support for our findings.